The effects of overconfidence in job market signaling - an experimental approach - Silva, Rita Alexandra Gouveia da (2019)
The job market works under asymmetric information, making it hard for firms to know the real capabilities of the workers they hire. Workers can help overcome this asymmetry by signaling their productivity with investments in education. However, it’s fair to assume that workers sometimes miscalculate their own abilities, which disturbs the functioning of the signal. This study intends to analyze the effects of overconfidence amongst workers on the various parameters of the game by conducting an experiment. The results from the experiment suggest that the profits of both workers and firms will be greatly impaired as a consequence.